Response of early soybean cultivars to nitrogen fertilization associated with Bradyrhizobium japonicum inoculation - Mario Zuffo, Alan (2018)
In early soybean cultivars of high productive potential, the use of chemical nitrogen (N) fertilizer may be a critical factor to meet the crop N requirements for obtaining high yields. In order to determine the response of early soybean cultivars to doses and times of nitrogen fertilizer application, associated with the inoculation of Bradyrhizobium japonicum, two field experiments were conducted in a Quartzipsamment soil from the Brazilian tropical Savannah, during the 2016/2017 and 2017/2018 growing seasons. The experimental treatments were arranged in a 2 × 3 × 4 factorial scheme, being two soybean cultivars (BRS 1074 IPRO and ST 797 IPRO), three application times of N fertilizer (sowing, 30 and 50 days after the emergence) and four N doses (0 kg ha-1, 20 kg ha-1, 40 kg ha-1 and 60 kg ha-1). The following variables were evaluated: plant height, shoot dry matter, number of nodules, nodule dry matter, first pod height, number of pods, number of grains per pod, 1,000-grain mass, grain yield and harvest index. The use of N fertilizer did not improve the production components and did not increase the soybean grain yield, regardless of the doses and times of application. Therefore, it was concluded that, if efficient strains of B. japonicum are used in areas of first soybean crop, in a Quartzipsamment soil with medium-high fertility, especially with a relatively high N availability due to the mineralization of the soil organic matter, there is no need to apply starter or late doses of nitrogen fertilizer.